2006
DOI: 10.1136/ard.2005.048934
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous abnormalities in rheumatoid arthritis compared with non-inflammatory rheumatic conditions

Abstract: Background: Cutaneous abnormalities are common in rheumatoid arthritis, but exact prevalence estimates are yet to be established. Some abnormalities may be independent and coincidental, whereas others may relate to rheumatoid arthritis or its treatment. Objectives: To determine the exact nature and point prevalence of cutaneous abnormalities in patients with rheumatoid arthritis compared with those in patients with non-inflammatory rheumatic disease. Methods: 349 consecutive outpatients for rheumatology (205 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 34 publications
1
15
1
9
Order By: Relevance
“…We also found a lower incidence of CAE in AS and PsA patients compared with RA patients (Table ). Reports describe an increase in cutaneous lesions () and skin malignancies in RA patients () and an increase in the rate of infections, including cutaneous infections () and viral infections, especially herpesvirus (). The reason for this is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…We also found a lower incidence of CAE in AS and PsA patients compared with RA patients (Table ). Reports describe an increase in cutaneous lesions () and skin malignancies in RA patients () and an increase in the rate of infections, including cutaneous infections () and viral infections, especially herpesvirus (). The reason for this is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic involvement may present with extra-articular manifestation of various organs, including the lung, heart, kidney and skin [1]. Recent studies focusing on dermatological conditions in RA patients have identified a high prevalence of rheumatoid nodules (34%) and Raynaud phenomenon (17%) [2,3,4,5]. According to different studies, the frequency of leg ulceration in patients with RA may be up to 10% [6,7] compared to the prevalence of venous leg ulceration in the general population of approximately 1% [8]; thus, implying that patients with RA are at increased risk of developing ulcerations of the lower extremities leading to considerable morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in addition to the well-known specific and nonspecific cutaneous lesions, patients with RA had also been reported to exhibit a wide range of rare conditions such as dermatophytosis, erythema nodosum, alopecia, vitiligo, contact dermatitis, urticaria, tylosis, and clavus. 2,6,7 Lichen amyloidosis is a type of primary localized cutaneous amyloidosis in which amyloid, a fibrillar proteinaceous material, is deposited solely in the skin, without associated systemic involvement. 8,9 It is characterized by multiple pruritic discrete hyperkeratotic papules that coalesce into plaques, most commonly located on the anterior legs, upper back, forearms, and thighs.…”
Section: Discussionmentioning
confidence: 99%